1997
DOI: 10.2113/gsecongeo.92.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of oxidized- and reduced-type granites

Abstract: The genesis of oxidized-type (magnetite series) and reduced-type (ilmenite series) granites is discussed on the basis of thermodynamic considerations. We show that SO2 in the magma can oxidize augitc to form magnetite with decreasing temperature because the SO.•-H.•S buffer line intersects with the augitc-magnetitequartz buffer line on a 1/T -fo• diagram. When the magma contains SO.• above 250 ppm and the f% is constrained by the SO2-H.•S buffer, the magma forms oxidized-type granites (>0.2 modal % magnetite).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 8 publications
(13 reference statements)
0
35
0
3
Order By: Relevance
“…Takagi and Tsukimura (1997) discussed that it plays an important role in buffering the redox condition and thus in defining the granitoid type whether the oxidized sulfur species or the reduced species is dominated in the granitic magma. The high activity of oxidized sulfur in the intermediate to silicic magmas in the western Luzon arc since the early stage of magmatic differentiation is suggested by the high SO 3 contents in microphenocrystic apatite.…”
Section: Discussionmentioning
confidence: 99%
“…Takagi and Tsukimura (1997) discussed that it plays an important role in buffering the redox condition and thus in defining the granitoid type whether the oxidized sulfur species or the reduced species is dominated in the granitic magma. The high activity of oxidized sulfur in the intermediate to silicic magmas in the western Luzon arc since the early stage of magmatic differentiation is suggested by the high SO 3 contents in microphenocrystic apatite.…”
Section: Discussionmentioning
confidence: 99%
“…Takagi and Tsukimura (1997) calculated that the CH 4 -CO 2 buffer line always lies far below the NNO buffer line and just below the FMQ buffer line on a log f O 2 -1/T diagram under magmatic conditions. The redox paths of granitic magma, during the cooling process, were closely discussed by many previous studies (Honma, 1974;Kanisawa, 1976;Shimazaki, 1976;Ishihara, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Takagi and Tsukimura (1997) showed that the oxygen fugacity of magma is constrained by a gas buffer in the magma, and they proposed that dominant H2S and low SO 2 (<250 ppm) granitic magma would form ilmenite-series, while high SO 2 (250-1,700 ppm) magma yield magnetite-series. This proposal may explain regional distribution patterns of two series of granitoid formed from two genetically distinct magmas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur in the magnetite-series magma may possibly be present as sulfate originated ultimately in sea-water sulfate (Sasaki and Ishihara, 1979;Takagi and Tsukimura, 1997) and moved out from the magma chamber to the overlying alteration zones. Such magmatic sulfur is combined with chalcophile element and concentrates chalcopyrite in the alteration zone.…”
Section: Petrochemistry Of Granitoids In the Other Regionsmentioning
confidence: 99%